2006
DOI: 10.1186/1477-7827-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Prostate response to prolactin in sexually active male rats

Abstract: Background: The prostate is a key gland in the sexual physiology of male mammals. Its sensitivity to steroid hormones is widely known, but its response to prolactin is still poorly known. Previous studies have shown a correlation between sexual behaviour, prolactin release and prostate physiology. Thus, here we used the sexual behaviour of male rats as a model for studying this correlation. Hence, we developed experimental paradigms to determine the influence of prolactin on sexual behaviour and prostate organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…As we have previously shown [1], PRL is one of the several hormones that stimulate this gland, and it has now been found that the stimulation is highly correlated with the sexual life of the subject. In male rats with a single sexual encounter, the fluctuation of serum PRL shows a transient increase, suggesting a long refractory period that makes the system controlling the release of PRL unresponsive to further mating stimuli [1]. Now, in this work we found that subjects engaged in continued sexual behavior over longer periods of time showed different serum PRL profiles, such that PRL levels were constantly elevated during mating.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…As we have previously shown [1], PRL is one of the several hormones that stimulate this gland, and it has now been found that the stimulation is highly correlated with the sexual life of the subject. In male rats with a single sexual encounter, the fluctuation of serum PRL shows a transient increase, suggesting a long refractory period that makes the system controlling the release of PRL unresponsive to further mating stimuli [1]. Now, in this work we found that subjects engaged in continued sexual behavior over longer periods of time showed different serum PRL profiles, such that PRL levels were constantly elevated during mating.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the periodic execution of copulation during the sexual life of the subject is influenced by the constant elevated levels of serum PRL. However, serum PRL levels differed, so that in the case of males beginning their sexual life, the transient increase in serum PRL could reach up to 80 ng/ml [1], whereas subjects engaged in sexual behavior showed sustained elevation of serum PRL up to 30 ng/ml. Thus, periodic sexual behavior seems to modify the neuroendocrine circuit underlying PRL release.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations